If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(5 + -1) = t Combine like terms: 5 + -1 = 4 6(4) = t Multiply 6 * 4 24 = t Solving 24 = t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 24 + -1t = t + -1t Combine like terms: t + -1t = 0 24 + -1t = 0 Add '-24' to each side of the equation. 24 + -24 + -1t = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -1t = 0 + -24 -1t = 0 + -24 Combine like terms: 0 + -24 = -24 -1t = -24 Divide each side by '-1'. t = 24 Simplifying t = 24
| 5w+2=11 | | 2j+5=k | | 4c^2-12cd+9d^2=0 | | 3m-9=2m-4 | | 8+6a=6a+8 | | 8+6a=2a+8 | | 2y-2x-2z= | | 7(y-2)=5(y+4) | | 2(x-7)=x-12 | | 2(3p-1)=22 | | 4(n-3)=36 | | r^2=-35-12r | | 5(2n-1)=25 | | 4(a-4)=8 | | 3(x+7)+x+3=18 | | 7(x-8)=6(x+2) | | 6(a+7)=5(a-3) | | 2(a+1)=a+2 | | 8(3-x)=7(x-6) | | 1oy-6=5y+19 | | 8(3x-1)-(6x-8)=5(4x-30) | | 2x-14=x-12 | | 0.6*4.75+0.4*(x*22.5)+0.4*(1-x)*20=0 | | 12p-3=5p+32 | | 2+56+6= | | 0.6*4.75+0.4*(x*42.5)+0.4*(1-x)*20=0 | | 11m-6=7m+14 | | 7y-3=4y+15 | | 4a-3=3a+9 | | p^2+3p=18 | | 0.3xX=63 | | 9(2w+5)-2w=7(8-w)-10w |